PHOTOGRAPHIC OBSERVATIONS OF SOLAR SYSTEM BODIES AT THE MAIN ASTRONOMICAL OBSERVATORY OF NAS OF UKRAINE: FINAL RESULTS - Golovnia, V.; Yizhakevych, O.; Shatokhina, S.; Andruk, V. (Одеські астрономічні публікації, 2017)
Astrometric photographic observations of Solar system bodies in the frame of different programs were made at MAO NAN of Ukraine during 1950-2005. 9245 plates with the images of planets and their natural satellite, Moon, minor planets, comets and artificial satellites were obtained and processed in the late 20th century. At the beginning of the 21st century, the UkrVO Joint Digital Archive (JDA) was created, which is accessible at the МAO NAS resources (http://gua.db.ukr-vo.org/archivespecial.php). To digitize the plate archive for the JDA database, flat bed scanners were used and the software was specially de-veloped on the basis of the LINUX/MIDAS/ROMAFOT software for the processing of wide-field images, as well as searching for the images of minor planets and comets on the Northern sky survey program plates. Up to the present time, the photographic plates with images of outer planets and their satellites have been re-processed. The final result of the long-lasting program of the photographic positional observations of Solar system bodies are summarized and presented in this publication.